A Novel Way to Prepare Visible‐Light‐Responsive WO3/TiO2 Composite Film with High Porosity. Issue 2 (25th April 2013) - Luo, Qiang; Cai, Qizhou; He, Jian; Li, Xinwei; Chen, Xidi; Pan, Zhenhua; Li, Yujie
<x xml:space="preserve">Abstract</x> Amorphous oxide film was prepared on the titanium substrate by plasma electrolytic oxidation (PEO) technology in acidic electrolyte consisting of tungstate and then subject to calcination in air. Films were characterized by scanning electron microscopy, energy dispersive X‐ray, X‐ray diffraction, X‐ray photoelectron spectroscopy, photoluminescence, and UV‐Vis DRS before and after calcination, respectively. Calcined film consisted of anatase and WO3, showing more open structure compared with uncalcined film. Furthermore, the absorption edge of calcined film was shifted to visible light region and the recombination of photo‐induced carriers was inhibited effectively, resulting that WO3/TiO2 composite film produced by PEO technology and calcination should be effective as a visible‐light‐responsive photocatalyst.